In Situ Flame Temperature Measurements Using a Mid-Infrared Two-Line H2O Laser-Absorption Thermometry. Issue 3 (4th March 2018) - Ma, Liuhao; Ning, Hongbo; Wu, Junjun; Ren, Wei
ABSTRACT: A mid-infrared two-line thermometry based on H2 O absorption was developed for in situ and sensitive temperature measurements of laminar flames. The H2 O absorption lines in v 3 fundamental band were systematically investigated and a new promising line pair (4029.52 cm –1 and 4030.73 cm –1 ) was selected to achieve strong absorption line-strength and high-temperature sensitivity over the temperature range of 1000–3000 K. This line pair was readily assessed by a single current scan of a distributed feedback laser near 2.5 μm. The scanned-wavelength laser absorption strategy was adopted for temperature measurements for both laminar sooting and non-sooting flames. This optical sensor was applied in measuring various flame conditions including CH4 /air and C2 H4 /air premixed flames (Ф = 0.8–1.2), C2 H4 /air sooting flames (Ф = 1.78–2.38), and partially premixed flames. Our measurements were in good agreement with thermocouple measurements for all the flame conditions. In addition, numerical simulations using the detailed chemical kinetic mechanisms (CH4 flame: GRI 3.0, C2 H4 flame: USC 2.0) were conducted to validate the experimental results.